Local economic benefit in shopping and transportation: a study on tourists’ expenditure in Melaka, Malaysia - Mohamed Osman, Mariana; Ab Rahman, Syakir Amir; Bachok, Syahriah; Ibrahimy, Muhammad Ibn (Elsevier, 2016)
This study investigated the tourists’ expenditure pattern in Melaka city and its contribution to the local economy. Chi-square Automatic Interaction Detection (CHAID) was chosen to model the interaction for domestic and inbound tourists in transportation and shopping sectors and subsequently identify the local economic benefits. Results revealed that the tourists exhibited low expenditure levels (RM18.50 and below) in the transportation sector, contributing less benefits to the local economy as most tourists chose to walk. The tourists also demonstrated low levels of expenditure (RM75 and below) in the shopping sector, but contributed to the local economy by shopping in Jonker Street.